Games Asyik Matematika: Pengabdian Kepada Masyarakat di SD Negeri Jatirangga 3 Bekasi - Dyah Anungrat Herzamzam; Evi Faujiah (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
Based on the analysis of the situation that occurred, the lack of socialization related to the 2013 Curriculum made many elementary school teachers including SDN Jatirangga 3 Bekasi City do not understand. Teachers of SDN Jatirangga 3 in Bekasi City have not been able to apply the 2013 Curriculum in the learning process. Based on a request letter from SDN Jatirangga 3, the Chairperson of STKIP Kusuma Negara to send PGSD lecturers to provide training to teachers there regarding the 2017 Revised 2013 Curriculum in particular. So the PGSD Study Program, STKIP Kusuma Negara sent 4 lecturers to become resource persons for the training. This training was given the theme